Консультативна юрисдикція Європейського суду з прав людини - Бойко, Інна Семенівна; Бойко, І. С.; Boiko, Inna S.; Boiko, I. S. (Одеса : Гельветика, 2020)
У статті проаналізовано консультативну юрисдикцію Європейського суду з прав людини. Науково-професійне тлумачення норм Конвенції про захист прав людини і основоположних свобод (ст. ст. 47–49), Протоколу № 16 до неї, правил Регламенту Суду дало змогу класифікувати різновиди консультативної юрисдикції за суб’єктом права звернення до Суду: 1) консультативні висновки, які надаються за запитом Комітету Міністрів Ради Європи; 2) консультативні висновки, які надаються за запитом призначеного державою – учасницею Конвенції вищим судом або судовою установою, визначеного для цілей пункту 1 статті 1 Протоколу № 16 до Конвенції. Установлено, що консультативна юрисдикція ЄСПЛ не перетинається з компетенцією щодо розгляду спорів, тому перший запит від Комітету Міністрів Ради Європи був відхилений. Суд вирішив, що, оскільки запит стосувався критерію прийнятності звернень, тобто якщо в рамках механізму, встановленого Конвенцією СНД, справа вже прийнята до розгляду, то таке звернення підпадає під обмеження консультативної юрисдикції, передбаченої ст. 47 (2) Європейської конвенції про захист прав людини й основоположних свобод. Наступні два консультативні висновки, надані ЄСПЛ відповідно до ст. 47 Конвенції, стосувалися процедури обрання суддів Суду та мають прецедентне значення. Обґрунтовано, що ЄСПЛ виконує конституційну функцію, у межах якої він установлює стандарти у сфері захисту прав і свобод людини шляхом надання консультативних висновків. Саме ці документи створюються для того, щоб держави – учасниці Конвенції на національному рівні здійснили якісні зміни судових систем та судочинства, які, своєї чергою, допомагали б захистити права і свободи людини завдяки переходу з ex post (перед подією) на ex ante (після події) у вирішенні низки питань щодо тлумачення та застосування положень Конвенції на рівні певної держави. Просування конструктивного діалогу між Європейським судом з прав людини та національними судами або судовими установами слугуватиме подальшому впровадженню Конвенції про захист прав людини і основоположних свобод на національному рівні відповідно до принципу субсидіарності.

The article analyzes the advisory jurisdiction of the European Court of Human Rights. Scientific-professional interpretation of the norms of the Convention for the Protection of Human Rights and Fundamental Freedoms (Articles 47-49), Protocol № 16 thereto, Chapters IX, X of Rules of the Court allowed to classify the types of advisory jurisdiction according to the subject of the right to request: 1) advisory opinions requested by the Committee of Ministers the Court shall apply, in addition to the provisions of Articles 47, 48 and 49 of the Convention; 2) advisory opinions requested by courts or tribunals designated by Contracting Parties pursuant to Article 10 of Protocol No. 16 to the Convention. In accordance with Article 1 of Protocol No. 16 to the Convention, a court or tribunal of contracting party to that Protocol may request the Court to give an advisory opinion on questions of principle relating to the interpretation or application of the rights and freedoms defined in the Convention and the Protocols thereto. It has been established that the advisory jurisdiction of the ECHR does not intersect with the contentious jurisdiction of Court. Therefore, the first request from the Committee of Ministers of the Council of Europe was rejected. The Court held that since the request concerned the criterion of admissibility of applications, ie if, under the mechanism established by the Commonwealth of Independent States Convention, the case had already been accepted, such an application fell within the limitation of advisory jurisdiction under Article 47 (2) of the Convention. The following two advisory opinions issued by the ECHR under Article 47 of the Convention concerned the procedure for the election of judges of the Court and have precedent sense. It is substantiated that the ECtHR performs a constitutional function, within which it sets standards in the field of protection of human rights and freedoms by providing advisory opinions. It is these documents that are being created in order for the contracting parties to make qualitative changes in the judicial systems at the national level, which, in turn, would help protect human rights and freedoms by moving from “ex post” to “ex ante” in addressing a number of issues concerning the interpretation and application of the provisions of the Convention at the contracting party’s level. The promotion of a constructive dialogue between the European Court of Human Rights and national courts or tribunals will serve for the subsequent implementation of the Convention for the Protection of Fundamental Rights and Fundamental Freedoms at national level, in accordance with the principle of subsidiarity.
Бойко І. С. Консультативна юрисдикція Європейського суду з прав людини / І. С. Бойко // Юридичний вісник. - Одеса : Гельветика - 2020. - № 2. - С. 64-72.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; advisory opinions of the European Court of Human Rights; constitutional function of the European Court of Human Rights; case law; principle of subsidiarity; консультативні висновки ЄСПЛ; конституційна функція ЄСПЛ; прецедентне право; принцип субсидіарності